Usability Testing Situs Web Politeknik Negeri Batam Menggunakan Metode Eye Tracking - Fadli Suandi; Swono Sibagariang; Yessy Kusumah Amalia; M. Bambang Firdaus (JURNAL INTEGRASI, 2021)
The use of websites is now a necessity for many organizations so that information on these organizations can be seen and accessed by the wider community. To ensure the quality of the presentation of information on the website, we can take advantage of the use of an eye tracker in evaluating the usability of site visitors when interacting with website pages. This study aims to evaluate and analyze the results of usability testing by a number of respondents while doing user tasks and interacting with the website www.polibatam.ac.id using the eye tracking method. The method used includes 4 stages, starting with the initiation of needs, Pre-User Testing, User Testing and ending with the Post User Testing stage. After the test finished, all respondents can complete the user task with an average processing time of 4 minutes 33 seconds. From the results of the eye tracking analysis, there was a minor problem related to the naming of the user menu on the polibatam.ac.id website. The suggestion to improve the website www.polibatam.ac.id is to pay more attention to the naming of the main sub menu on the web page to be more specific so as not to cause confusion for website visitors.